Risk Management in Indian Agribusiness: Types and Coping Strategies - Uikey, Ashish Ashok (Research Advances and Challenges in Agricultural Sciences Vol. 5, 2024)
This chapter dives deep into the intricate landscape of risk management in agribusiness, recognizing the ever-evolving challenges faced by the agricultural sector. The multifaceted nature of risks, including production, market, regulatory, financial, and human resource risks, underscores the complexity of decision-making for farmers. Drawing on diverse socio-economic backgrounds, farmers' risk perceptions significantly influence the adoption of risk management strategies, with factors like age, education, culture, and institutional support playing pivotal roles. The chapter identifies and explores the types of risks prevalent in Indian agribusiness, elucidating the dynamics of production risks influenced by weather, pests, and technological advancements, market risks arising from price fluctuations, regulatory risks tied to governmental actions, financial risks associated with credit and exchange rates, and human resource risks linked to personnel unavailability. A comprehensive analysis of risk management strategies is presented, encompassing crop insurance, crop diversification, water management, technology adoption, market linkages, credit and financial management, capacity building, and policy support. While farmers employ these strategies to navigate uncertainties, the chapter acknowledges that implementing risk management practices incurs costs and may impact productivity. Ongoing research and dialogue are deemed essential to refine and optimize risk management approaches, ensuring the resilience and sustainability of agribusinesses in the face of evolving challenges.